Left Sided Appendicitis — A Surgical Dilemma: Case Report - Zohaib Mushtaq; Muhammad Zeeshan Sarwar; Yaseen Rafi; Syed Asghar Naqi (Journal of the Pakistan Medical Association, 2021)
Published in May - 2021